The Effect Of Tiktok Content Based Social Media Marketing On Dear Me Beauty Brand Image - Nadhira Alya Zahira Danuwijaya; Tarandhika Tantra (LPPM STIE EKA PRASETYA, 2023)
The large number of active social media users in Indonesia are taking advantage of opportunities as marketing media. One of them is through the Tiktok application. Because the Tiktok application is the right medium in marketing strategies, especially for the Dear Me Beauty brand. The purpose of this study was to find out how influential social media marketing in the form of Tiktok content is on the formation of a brand image for Dear Me Beauty products. This research was conducted using multiple linear regression analysis techniques and descriptive analysis with an associative approach. The results of this study were obtained from the large number of 400 respondents who resulted that social media marketing in the Tiktok application is very influential in forming a brand image for Dear Me Beauty products, especially in content sharing variable in spreading Tiktok social media content. For future researchers, it is suggested to study more deeply related to what factors can influence the formation of brand image. For Dear Me Beauty, it is hoped that this will be a unique consideration, always improving the quality of Tiktok ads to attract consumers' attention and always being consistent with a good sales system to improve performance that is considered unsatisfactory.